2022
DOI: 10.1007/s11103-022-01241-4
|View full text |Cite
|
Sign up to set email alerts
|

Rapid sequence evolution is associated with genetic incompatibilities in the plastid Clp complex

Abstract: The plastid caseinolytic protease (Clp) complex plays essential roles in maintaining protein homeostasis and comprises both plastid-encoded and nuclear-encoded subunits. Despite the Clp complex being retained across green plants with highly conserved protein sequences in most species, examples of extremely accelerated amino acid substitution rates have been identified in numerous angiosperms. The causes of these accelerations have been the subject of extensive speculation but still remain unclear. To distingui… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 74 publications
1
7
0
Order By: Relevance
“…Abdel‐Ghany et al. (2022) studied sequence variability of the plastid caseinolytic protease (Clp) complex, which plays an essential role in maintaining protein homeostasis and comprises both plastid‐encoded and nuclear‐encoded subunits. They used plastome transformation to partially replace the native clpP1 gene in tobacco with counterparts from different Silene species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdel‐Ghany et al. (2022) studied sequence variability of the plastid caseinolytic protease (Clp) complex, which plays an essential role in maintaining protein homeostasis and comprises both plastid‐encoded and nuclear‐encoded subunits. They used plastome transformation to partially replace the native clpP1 gene in tobacco with counterparts from different Silene species.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies of this complex further indicated that the rates of clpP1 evolution strongly correlate with the amino acid sequence divergence in interacting nuclear‐encoded CLP counterparts in various angiosperms (Rockenbach et al., 2016; Williams et al., 2019). This may reflect the coevolution of genes involved in cytonuclear interactions to keep them functional (Abdel‐Ghany et al., 2022; Ceriotti et al., 2022; Forsythe et al., 2021; Sloan et al., 2014; Williams et al., 2019). Among the genes involved in the cytonuclear complexes, we were able to identify PSBW , involved in the PSII supercomplex, with a biased expression in advanced generations, and differences in the amino acid sequence between Lolium and Festuca .…”
Section: Discussionmentioning
confidence: 99%
“…More targeted studies have also directly tested for genetic incompatibilities by generating chimeric enzyme complexes with subunits derived from two different species or complexes with an altered mix of paralogous subunits ( Kanevski et al 1999 ; Kim et al 2009 ; Lind et al 2010 ; Kacar et al 2017 ; Abdel-Ghany et al 2022 ). In such experiments, it is also possible to make comparisons between the effects of introducing a single foreign (or ancestral) subunit versus replacing an entire multisubunit complex ( Garcia et al 2022 ).…”
Section: Genetic Incompatibilities Exposed By Hybridization and Hgtmentioning
confidence: 99%
“…However, the same was not true for attempts using a large subunit gene from a more distant (cyanobacterial) donor, supporting the expectation that the age of divergence between donor and recipient lineages contributes to accumulation of genetic incompatibilities. More recently, experiments used flowering plants that differed dramatically in their historical rates of sequence evolution for the plastid-encoded ClpP1 protein as donors to replace the native tobacco copy in another plastid–nuclear enzyme complex (the caseinolytic protease), finding that a history of accelerated sequence divergence hindered functional replacement ( Abdel-Ghany et al 2022 ). By using donors from the same genus ( Silene ), this experiment controlled for divergence time, isolating effects of evolutionary rate variation.…”
Section: Genetic Principles That Determine Balance Between Incompatib...mentioning
confidence: 99%
“…The cytoplasmic genomes in S. conica also exhibit other distinctive features, including accelerated evolutionary rates, major structural changes, and extensive gene loss (Erixon and Oxelman 2008; Sloan, Alverson, Chuckalovcak, et al 2012; Sloan, Alverson, Wu, et al 2012). As such, this species has been a valuable model for studying how changes in cytoplasmic genomes can spur cytonuclear coevolution (Rockenbach, et al 2016; Havird, et al 2017; Abdel-Ghany, et al 2022).…”
Section: Introductionmentioning
confidence: 99%